Β-adrenergic-blocking drugs and melanoma: current state of the art. Issue 11 (November 2012) - De Giorgi, Vincenzo; Grazzini, Marta; Gandini, Sara; Benemei, Silvia; Asbury, Curtis D; Marchionni, Niccolò; Geppetti, Pierangelo
The purpose of this review is to present the preclinical, epidemiological and clinical data relevant to the association between β-blockers and melanoma progression. Preclinical studies have shown that β-adrenergic receptor (β-AR) signaling can inhibit multiple cellular processes involved in melanoma progression and metastasis. These observations have suggested the possibility that drugs originally intended for the treatment of cardiovascular disease, the β-AR blockers, may provide new therapeutic opportunities for the control of tumor progression. A large number of observational studies demonstrated the protective effect of β-blockers in breast cancer but, more recently, similar findings were also reported in other cancers such as prostate cancer and melanoma. With regard to melanoma, two recently published studies demonstrated a great reduction in the risk of disease progression for each year of treatment with β-blockers. The results from these studies have suggested a potential role for targeting the β-AR pathway in melanoma patients. Questions regarding the type of β-blocker or tumor characteristics, appropriate treatment paradigms and, most importantly, efficacy must be answered in randomized clinical studies before β-blockers can be considered a therapeutic option for patients with melanoma.